Analisis Keberlanjutan Sistem Pengelolaan Air Limbah Domestik Terpusat Skala Permukiman - M. Rafly Sarully Hidayat; Ahmad Soleh Setiyawan (Jurnal Serambi Engineering, 2024)
Domestic activities around DAS Citarum cause significant pollution and environmental damage. One of the strategies implemented is the treatment of domestic wastewater through SPALD-T on a settlement scale and one of the beneficiaries is Sindangpakuon village. Over time, there have been changes in the management structure, roles and activities of KPP as managers. An analysis was carried out to assess the impact of the completeness and activity of the KPP on its sustainability. Data collection was carried out through observation, interviews, questionnaires in analysing technical, institutional, financial, social-community participation, environmental aspects using RAPFISH and SWOT methods to diagnose and develop sustainability strategies. In the technical aspect of SPALD-T RW 06, 07 is considered quite sustainable and RW 10 is not sustainable, in the institutional aspect of all RWs is considered quite sustainable, in the financial aspect of RW 06 is considered quite sustainable and RW 07, 10 is not sustainable, in the social-community participation aspect of all RWs is considered quite sustainable and in the environmental aspect of RW 06, 07 is considered quite sustainable and RW 10 is sustainable. A strategy that can be applied by all SPALD-T is an aggressive strategy that uses strength to take advantage of opportunities. The research is expected to be one of the inputs for stakeholders in assessing and preparing sustainability strategies for community-based domestic sanitation programmes.